Pengaruh Direct Selling terhadap minat beli pada produk PT Surya Sentosa Primatama-Daihatsu Jambi - Vina Ersa; Mulyadi Raf; Sylvia Kartika (Jurnal Dinamika Manajemen, 2021)
This study aims to determine how the influence of direct selling on buying interest in PT Surya Sentosa Primatama Daihatsu Jambi products. This research is a descriptive study using quantitative methods. The object of this research is consumers who buy Daihatsu products in Jambi City Sipin. The sampling technique is non probability sampling. The number of samples used in this study amounted to 91 respondents from the population. The analysis technique used in this study is multiple linear regression analysis using SPSS software version 22.0. The results showed that simultaneously Repetitive Person to person selling variables ( ) Nonrepetitive person to person selling ( ), and Party Plans ( ) significantly influence Buy Interest (Y). Partially Repetitive Person variables to person selling ( ), Nonrepetitive person to person selling ( and Party Plans ( ) significantly influence Purchase Interest (Y).